Ethnomathematical Insights from the Geometric Architecture of the Sultan Mahmud Badaruddin II Museum - Dina Octaria; Zulkardi, Zulkardi; Ratu Ilma Indra Putri; Cecil Hiltrimartin (Department of Mathematics Education Program IPI Garut, 2025)
Pembelajaran geometri di sekolah sering kali bersifat abstrak dan kurang memanfaatkan sumber belajar kontekstual yang dekat dengan kehidupan sehari-hari siswa. Padahal, warisan budaya memiliki potensi besar sebagai media pembelajaran matematika yang menghubungkan konsep geometri dengan nilai-nilai lokal. Penelitian ini mengkaji konsep geometri dalam arsitektur Museum Sultan Mahmud Badaruddin II Palembang serta potensinya sebagai sumber belajar etnomatematika. Menggunakan pendekatan kualitatif dengan metode etnografi yang dimodifikasi, penelitian dilakukan melalui lima tahap utama: eksplorasi awal dan identifikasi informan, pengumpulan data lapangan, dokumentasi visual dan kontekstual, analisis data, serta interpretasi etnomatematis. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan dokumentasi visual, dianalisis dengan pendekatan domain dan taksonomi, serta diverifikasi melalui traingulasi sumber. Hasil menunjukkan elemen arsitektur museum, memuat konsep bangun datar, bangun ruang, kesebangunan, simetri, dan transformasi geometri yang terintegrasi dengan nilai budaya lokal. Temuan ini merekomendasikan integrasi museum dalam PjBL dan kurikulum berbasis kearifan lokal untuk meningkatkan keterlibatan siswa, identitas budaya, dan kompetensi guru. Geometry learning in schools often remains abstract and makes limited use of contextual resources that are closely connected to students’ daily lives. Cultural heritage holds significant potential as a medium for mathematics instruction, linking geometric concepts to local values. This study examines the geometric concepts embedded in the architecture of the Sultan Mahmud Badaruddin II Museum in Palembang and explores its potential as a learning resource within an ethnomathematics framework. Employing a qualitative approach with a modified ethnographic method, the research was conducted in five main stages: initial exploration and informant identification, field data collection, visual and contextual documentation, data analysis, and ethnomathematical interpretation. Data were collected through observations, semi-structured interviews, and visual documentation, analyzed using domain and taxonomic approaches, and verified through source triangulation. The results indicate that the museum’s architectural elements contain concepts of plane figures, solid figures, similarity, symmetry, and geometric transformations, all integrated with local cultural values. The study recommends integrating museums into PjBL and local wisdom-based curricula to enhance student engagement, strengthen cultural identity, and improve teachers’ competencies.